THE Analisis Potensi Kebangkrutan Dengan Menggunakan Metode Altman Z-Score, Springate Score, Dan Zmijewski Score (Studi Kasus Pada PT Hanson International Tbk) - Nurul Fitri (The Indonesia Capital Market Institute, 2021)
This study aims to describe the potential for bankruptcy using the Altman Z-score, Springate score, and Zmijewski score method, and to see which method has the highest level of accuracy. This type of research is qualitative using secondary data, namely data on the annual financial report publication of PT Hanson International Tbk for the period 2015-2018. The sampling technique is side purposive. Buy using data analysis techniques Altman Z-score, Springate score, and Zmijewski score method. The results of this study indicate that there are difference in predicting the potential bankruptcy of PT Hanson International Tbk for the 2015-2018 period from each method used between the Altman Z-score, Springate score, and Zijewski score method. and the rate of the Springate score method which has the highest level of 100% with an error type of 0%.